Teaching English in the Philippine: Pre-Service Teachers’ Identity Development During the International Teaching Practicum - Triyoga, Arilia; Hidayati, Ratri Nur; Widyanesti, Soffi (Journey: Journal of English Language and Pedagogy, 2024)
English pre-service teachers find teaching English abroad to be a memorable experience. It influences the type of teacher they will become in the future. Through the perspective of teacher identity, this study aims to describe how two Indonesian pre-service teachers in the English education department, during a teaching practicum in the Philippines, developed their teacher identity and how they overcome the challenges. This research focused on two fourth-year students from the English Education department of a private university in Yogyakarta who completed a one-month international teaching practicum in the Philippines. The data were gathered through semi-structured interviews and subsequently investigated thematically from the perspective of the teachers' identities, and then presneted narratively. It was discovered that the biographies of the pre-service teachers served as the starting point for their teachers' identity development. Throughout the international teaching practicum, the development of their teacher identity was influenced by their emotional reactions, their teaching methods, and their symbolic representation. In the international teaching setting, the student teacher received psychological and technical assistance to overcome the challenges of their practice. This support played a crucial role in the successful completion of the program and contributed to the development of their professional identity as teachers. The findings demonstrate the importance of international teaching experience, prompting universities to prioritize the teaching practicum. Additionally, the university should expand its international exchange programs, focusing on teaching practicum programs.